PENGARUH KINERJA PRODUK, PELAYANAN DAN SUMBERDAYA MANUSIA TERHADAP NIAT PEMBELIAN ULANG MELALUI CITRA PERUSAHAAN DAN KEPUASAN PELANGGAN PT ASURANSI JIWASRAYA - Ida Aju Brahma Ratih (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
The objectives of this study are to examine the effects of product, service and human resource performances on repurchasing intention through company image and customer satisfaction of PT Asuransi Jiwasraya. 115 customers from 245 customers of six branch offices of PT Asuransi Jiwasraya Surabaya Region were selected as respondents, using simple random sampling technique and participated in this study. The data were collected in 2004 using questionnaires and analyzed using Structural Equation Modelling (SEM).The result of this study proved that product, service as well as human resource performances had positive and significant effects on company image as well as on customer satisfaction. Customer satisfaction also had a significant effect on repurchase intention. However, company image had insignificant effects on repurchase intention. Therefore, out of nine hypotheses proposed, only one hypothesis was rejected, which was the significant effect of company image on repurchase intention. This finding reminded  an important empirical evidence on the development of customer behavior theories and practices.